“Barzanji Bugis” dalam Peringatan Maulid: Studi Living Hadis di Masyarakat Bugis, Soppeng, Sul-Sel - Ahmad Muttaqin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Prior to reading this paper, it is important to realize that hadis as source of islamic teachings has been expressed on cultural varieties. This aims to explore how the Bugis society views both the meaning of Maulid (prophetic birthday celebration) and the reading of Bugis-barzanji and to analyze the acculturation between both islamic teaching and Bugis culture on reading the Barzanji in Maulid. This research uses acculturational concept to explore deeply and briefly how islamic teaching and local tradition produce the new religious cultural practices. This concludes that first, barzanji in Bugis society is one of religious cultural practices regarded as secred tradition excepting in Maulid. Second, the Bugis-barzanji read on maulid celebration in order that society are able to understand easily the barzanji containing sīrah nabawiyyah (prophetic history) is one of living-hadis phenomena.